Estrogen Disrupts the Inhibition of Fear in Female Rats, Possibly through the Antagonistic Effects of Estrogen Receptor α (ERα) and ERβ - Toufexis, Donna J. (J Neurosci, 2007)
The ambiguous role of estrogen in emotional learning may result from opposing actions of estrogen receptor α (ERα) and ERβ. Using a fear-conditioning paradigm called the AX+, BX− discrimination, in which cue A comes to elicit fear and cue B becomes a safety signal, we examined the effect of 17β-estradiol (E) and selective ERα and ERβ agonists on excitatory and inhibitory fear learning. Gonadectomized (GDX) male and female rats implanted with E or selective ERα or ERβ agonists were trained on the AX+, BX− discrimination and tested periodically to A, B, and AB. GDX sham-implanted male and female rats and GDX E-implanted males, but not GDX E-implanted females, exhibited less fear to AB than to A, suggesting that estrogen interferes with generalization of safety signals in female rats. ERα and ERβ agonists disrupted discrimination learning in both sexes. ERα-implanted groups had higher fear responses to all cues than did ERβ-implanted groups, suggesting that these two receptors have opposing effects in aversive discrimination learning. In contrast, neither E nor ERα and ERβ agonists affected single-cue fear conditioning in either sex. These data suggest that E does not enhance fear in emotional learning but acts to disrupt the inhibition of fear in females only.